A comparison of two algorithms for the simulation of bending-active structures. Issue 2 (June 2018) - Cuvilliers, Pierre; Yang, Justina R.; Coar, Lancelot; Mueller, Caitlin
Bending-active structures, made from elastically bent materials such as fiberglass rods, offer exciting opportunities in architecture because of their broad formal palette and ease of construction. While they have been relevant since Frei Otto's Mannheim Multihalle (1974), recent computational developments that help simulate active-bending processes have renewed interest in them. Such tools are important because they can replace time-consuming and imprecise physical modeling processes. However, physically meaningful simulations, using real materials and full scale, are difficult to create, and there are no good mechanisms to reveal when a simulation is inaccurate. This article offers a conceptual and numerical study of two popular contemporary algorithms for simulations of bending-active structures, mainly through a comparison of their results on the planar elastica. We then offer guidelines on best practice modeling settings and demonstrate possibilities and pitfalls through an architectural-scale case study.